Overcoming the problem of cultural untranslatability in Burnett’s the secret garden from English into Indonesian - Nadia Khumairo Ma'shumah; Sajarwa Sajarwa (JOALL (Journal of Applied Linguistics and Literature), 2022)
This study aimed at investigating the untranslatable cultural terms found in the novel from English into Indonesian since not all cultural terms in Source Text can be fully transferred into Target Text as well as the translator’s decision to overcome the problem of untranslatability since English and Indonesian have very different cultural concepts. This study was a data-driven study by using The Secret Garden’s novel written by Burnett (1911/2019) as the Source Text (ST) and its Indonesian translation by Kusumawardani (2020) (under the same title) as the Target Text (TT). The data were analyzed by using descriptive-mix-comparative methods that combined the theory of Newmark’s (1988) cultural terms categorization and Newmark’s (1988) translation procedures. As a result, to overcome the problem of cultural untranslatability, the translator frequently employs transference, naturalization, and notes procedures. From in-depth analysis, transference by retaining the SL’s cultures in the TL is used to avoid mistranslation because the lacks a formally corresponding feature. Naturalization is used by adapting the SL cultural-specific words to the TL's normal pronunciation and morphology because there are designation similarities in both the SL and the TL. Meanwhile, notes in the form of in-text annotations and footnotes were used to strengthen the translator's role by highlighting her in the translation results. Nevertheless, notes are commonly used in conjunction with naturalization to reduce strangeness, as leaving too many untranslatable cultural references weakens the translation result.